2016
DOI: 10.1007/s00203-015-1176-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of salinity and osmotic stress on the plant growth-promoting bacterium Gluconacetobacter diazotrophicus PAL5

Abstract: Plant growth-promoting bacteria (PGPB) represent a promising alternative to the massive use of industrial fertilizers in agriculture. Gluconacetobacter diazotrophicus is a PGPB that colonizes several plant species. Although this bacterium is able to grow at high sucrose concentrations, its response to environmental stresses is poorly understood. The present study evaluated G. diazotrophicus PAL5 response to stresses caused by sucrose, PEG 400, NaCl, KCl, Na2SO4 and K2SO4. Morphological, ultrastructural and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Since we cultured many potentially pathogenic fungi from the plant material used in this study (B. U. Furtado, S. Szymańska, and K. Hrynkiewicz, unpublished work), we suggest that mitigation of excess oxidative stress by endophytic bacteria may be beneficial for the host. The greater frequency of oxidative stress response genes in root bacterial communities suggests that the plant response to bacteria is the more important source of stress than salinity, which is higher in shoots (58). However, why the genes involved in the rest of pathways are apparently more common in roots than in shoots still remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Since we cultured many potentially pathogenic fungi from the plant material used in this study (B. U. Furtado, S. Szymańska, and K. Hrynkiewicz, unpublished work), we suggest that mitigation of excess oxidative stress by endophytic bacteria may be beneficial for the host. The greater frequency of oxidative stress response genes in root bacterial communities suggests that the plant response to bacteria is the more important source of stress than salinity, which is higher in shoots (58). However, why the genes involved in the rest of pathways are apparently more common in roots than in shoots still remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of CHAP on the NaCl permeability of bacteria was detected as modified protocol as follows [31]. 100 μL of bacterial suspensions (1 × 10 6  CFU mL −1 ) with 1/2 × MIC of CHAP were added to 96-well plates and the bacterial suspensions with no CHAP as control.…”
Section: Methodsmentioning
confidence: 99%
“…Genome sequencing confirmed that Acetobacter sp. Pal5 was able to promote plant growth (Oliveira et al, 2016). Possibly due to its relatively small genome size, it has to dependent on its plant host closely to sustain life.…”
Section: The Ability Of Endophytic Bacteria On Nitrogen Fixationmentioning
confidence: 99%